An Exploration Of Pharmacists’ Readiness In Providing Addiction Counseling At The Methadone Dispensing Facilities In Kedah - Sareh Safwan Bin Abu Seman
This study is aimed to explore pharmacists’ perceptions in terms of their readiness to provide addiction counseling services to Methadone clients at the MD facilities in Kedah. The total number of participants involved in this study was six (6), comprising pharmacists aged 34–37 years who were in charge of methadone dispensing across six districts in Kedah. An open-ended semi-structured interview process was used to gather data from the pharmacist. This study is conducted qualitatively, and a non-probabilistic, purposive sampling technique was used. Qualitative data from the participants’ interview transcripts were analyzed manually by using Microsoft Word 365 for Windows 11 through thematic analysis and coding as well as descriptive demography. Weiner’s theory of organizational readiness has been used as the conceptual framework to guide this study. The study findings indicate that there are several main themes identified that describe pharmacists' perception of their readiness in terms of their role and tasks in providing addiction treatment. Next, the main aspects that contribute to the pharmacist's readiness to change in providing addiction counseling and, finally, the strategies are taken by the pharmacist to explore their opportunities to improve competency in their profession. In conclusion, there is a limited organizational readiness to implement addiction counseling because of considerable variation in both organization and pharmacist change efficacy and change commitment as well as restrictions in many contextual conditions. Furthermore, it has also been found that the structure and contents of the guided theory of organizational readiness by Weiner are relevant for this study. Several limitations and recommendations for future research are also discussed.